A Unifying Approach to the Empirical Evaluation of Asset Pricing Models - Peñaranda, Francisco; Sentana, Enrique (The Review of Economics and Statistics, 2015)
Regression and SDF approaches with centered or uncentered moments and symmetric or asymmetric normalizations are commonly used to empirically evaluate linear factor pricing models. We show that unlike two-step or iterated GMM procedures, single-step estimators such as continuously updated GMM yield numerically identical risk prices, pricing errors, and overidentifying restrictions tests irrespective of the model validity and regardless of the factors being traded, or the use of excess or gross returns. We illustrate our results with Lustig and Verdelhan’s (2007) currency returns, propose tests to detect some problematic cases, and provide Monte Carlo evidence on the reliability of asymptotic approximations.